META ANALYSIS OF THE EFFECTIVENESS OF CURCUMIN IN COVID 19 PATIENTS - Eko Priyono; Sukur Ma’mun; Mila Desi Anasanti (Kohesi: Jurnal Sains dan Teknologi, 2023)
Background: As SARS-CoV-2 virus (COVID-19) emerged and spread widely, chaos began to wreak havoc globally. Because the health emergency area persuaded the WHO to officially declare it a global pandemic, the COVID-19 epidemic had severe impacts. However, research on drugs is still minimal and as a result herbal medicines are emerging as the closest and fastest alternatives around.Objective: This study aims to evaluate the acceleration of recovery in patients with the COVID-19 pandemic with curcumin. Method: To conduct a literature search, various sources such as PubMed, Google Scholar, Science Direct, Cross Ref and Web of Science and utilize the PRISMA methodologyResults: Seventy RCTs (Randomized Controlled Trials) were included in the quantitative analysis study during the COVID-19 pandemic. Although there was significant variation between studies, they all had a low risk of bias. Analysis of forest plots before and after the intervention showed a non-significant effect (p-Val=0.0672) with a Standardized Mean Difference (SMD) of 0.57 (95% CI: 0.46; 0.67). This shows that curcumin did not significantly reduce the cure score among patients exposed to the COVID-19 pandemic. And heterogeneity is not significant (p-Val = 0.0005).Conclusions: This meta-analysis includes outcome-based evidence regarding curcumin treating patients among the COVID-19 population, as indicated by the lower ranking. Given the less promising results and potential to significantly enhance healing, curcumin therefore requires a broader perspective.